O enunciado verbovocovisual na/pela construção midiática do estereótipo Lula - (:unkn) unknown (Universidade Federal de Goiás, 2017)
The short-film is the outline that allows several sayings to come across and initiate a favorable domain to duel where the other, a responsive receptor and responsible, not inert in the discourse, may reflect and/or depict other realities. Before this wide field of relations, the construction of the stereotype meets a favorable area to the construction of sense effects under a diversity of visual extracts, verbal and vocal. In other words, entitled as verbovocovisual that it’s not about an outer language device, by contrast, it’s the enunciation capable of showing ideologies, genre, historical-social relations and the formation of collective representations. In these terms the present master degree dissertation entitled “The verbovocovisual utterance in/by media construction of Lula’s stereotype” regarding the interpretation and analyses dialogical-dialectic of the short-film “The three little pigs Lula version”, establishing connection with the Self that does not exist without the other in a continuous process that echoes in the sayings of the exteriority which is another meeting point between the innerness in the identity’s constitution. So, the audiovisual utterance is a discursive genre as it is a result of human activity and it’s formed by a singular esthetic that establishes in a relation between the most varied discourses, politics, literary and humoristic in the construction of a stereotyped collective representation of declared forms that is placed in history and form the architectonic character of Lula. In order to confirm this construction, we have at hand a theoretical research regarding Bakhtin’s basis corresponding to the interpretative and analytic effort of dialogic relations in/by the audiovisual media that corroborates to the construction of stereotypes perpetrated by temporality and by space in which one sign may convert in an ideological, not as a concluded materialism in its object represented, but in the relation with the social while converting into a symbol. Delivering to something exterior to its own materiality as an object, thus being ideological (BAKHTIN, 2014). Therefore, our reflection theoretical methodologic that constitute our analyses, considers the conceptions of dialogism, ideological sign, discursive genre and utterance (BAKHTIN, 2011; 2013; 2014; BAKHTIN/VOLOCHÍNOV, 2014; VOLOSHINOV, 1976; VOLOSHINOV, 2005), regarding stereotype (AMOSSY, 2005; AMOSSY e PIERROT, 2011), scenography, (MAINGUENEAU, 2005; 2008a; 2008b) and humor (CHARAUDEAU, 2006; 2007; 2009), this last one as effect of senses that contribute to the constitution of a stereotyped collective representation.
The verbovocovisual utterance in/by media construction of Lula’s stereotype
Keywords: Dialogismo; Verbovocovisual; Estereótipo; Curta-metragem; Dialogism; Verbovocovisual; Stereotype; Short-film; LINGUISTICA::FISIOLOGIA DA LINGUAGEM